The lives of things on Pulau Ujir; Aru’s engagement with commercial expansion - Whittaker, Joss R. (UI Scholars Hub, 2019)
In places with limited access to manufactured goods, people must develop creative strategies to make the most of available materials, both those produced by humans and those taken from the natural world. Although Pulau Ujir, in the Aru Islands, has a long history of engagement with global trade networks, until recently the community’s access to manufactured goods was limited and infrequent. As a result, in the past objects there tended to take on new lives, and still do today: they are modified, re-purposed, and recycled in ingenious ways. This article explores the relationship between people and things in Ujir from the perspectives of object biography and Actor Network Theory. I argue that the complex “life stories” of material things in such conditions of scarcity deserve special attention, because they may explain not only puzzling archaeological phenomena, but also aspects of the social lives of the people who used and reused them. Two modified and repurposed fragments, one of porcelain and one of glass, serve as examples.